Development of a "Model for Improving Quality of Life" for Stroke Patients Based on Preventive Efforts - Siagian, Hotmaida; Wilda, Yetty; Sulystiono, Dony; Saragih, Lenni (Health Notions, 2017)
Stroke in Indonesia is the third leading cause of death after heart disease and cancer. High rates of death and stroke-related disabilities are related to pathophysiological processes that occur in brain tissue. Changes in blood flow in the brain cause disruption of the nervous system. Such disturbance may result in permanent disability of the device in the form of paralysis. Physical changes that are often experienced by the patient is paralysis of motion, loss of swallowing ability, cognitive disturbances, and psychological disorders. These conditions will affect the psychological health and quality of life of patients. This research was conducted in 2 stages. The first stage is done by using Partial Least Square test to see the variable that influence the ability of patient and family in doing stroke prevention. The sample size used was 60 people taken by accidental sampling. The second stage is a pre-experiment that compares the conditions before and after treatment using t-test. The results showed that the predisposing factor (self efficacy and cues to action) had an effect on the behavior of stroke prevention; reinforcing factors (family roles) affect the behavior of stroke prevention; enabling factors (health promotion) affect the behavior of stroke prevention.